2020
DOI: 10.3390/jcm9030680
|View full text |Cite
|
Sign up to set email alerts
|

Early Aspirin Discontinuation Following Acute Coronary Syndrome or Percutaneous Coronary Intervention: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: The respective ischemic and bleeding risks of early aspirin discontinuation following an acute coronary syndrome (ACS) or percutaneous coronary intervention (PCI) remain uncertain. We performed a prospero-registered review of randomized controlled trials (RCTs) comparing a P2Y 12 inhibitor-based single antiplatelet strategy following early aspirin discontinuation to a strategy of sustained dual antiplatelet therapy (DAPT) in ACS or PCI patients requiring, or not, anticoagulation for another indication (CRD4201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A relationship has traditionally been reported between ischemic and bleeding risks, suggesting that those patients who might benefit the more from longer or more intensive antithrombotic treatment are unfortunately also exposed to a higher bleeding risk [18]. On the contrary, it has recently emerged that early discontinuation of DAPT might lead to a significant reduction of bleeding, without a relevant impact on ischemic risk [19]. The plot thickens with AF patients with indication for long-term anticoagulation.…”
Section: Plos Onementioning
confidence: 99%
“…A relationship has traditionally been reported between ischemic and bleeding risks, suggesting that those patients who might benefit the more from longer or more intensive antithrombotic treatment are unfortunately also exposed to a higher bleeding risk [18]. On the contrary, it has recently emerged that early discontinuation of DAPT might lead to a significant reduction of bleeding, without a relevant impact on ischemic risk [19]. The plot thickens with AF patients with indication for long-term anticoagulation.…”
Section: Plos Onementioning
confidence: 99%
“…The meta-analyses of these trials have confirmed the significant reduction of bleeding and did not report any significant increase in term of ischemic event, although MI or stent thrombosis were numerically higher with DAT compare to TAT [46,66]. Consequent to this accumulation of data, the 2020 ESC NSTEMI guidelines have recommended to use a short duration of TAT (i.e., in-hospital or up to one week following PCI) in this high risk population, unless the patients also present a significant risk of ischemic risk event, and to promptly relay TAT with DAT based on the association of NOAC and P2Y 12 inhibitors for 6-12 months according to the bleeding risk ( Figure 2) [5].…”
Section: Pairing Chronic Oral Anticoagulation With Antiplatelet Therapymentioning
confidence: 90%
“…As a results, the benefice of sustained DAPT may translate into smaller absolute ischemic event risk reduction, potentially outweighed by the associated increased risk of bleeding [39]. Based on the rational that aspirin may add only limited platelet inhibition when associated to potent P2Y 12 inhibitors, several large RCT have evaluated the safety and efficacy or early aspirin discontinuation, after 1 to 3 months of DAPT, with potent P2Y 12 inhibitors monotherapy prolongation [40][41][42][43][44][45][46][47].…”
Section: What Antithrombotic Regimen Following Pci?mentioning
confidence: 99%
“…Based on the results of RE-DUAL PCI [ 2 ], PIONEER-AF [ 3 ], AUGUSTUS [ 4 ], and ENTRUST-AF PCI [ 5 ] studies, and on two recent meta-analyses [ 27 , 28 ], a dual-pathway antithrombotic therapy (DAT) using a single antiplatelet agent (a P2Y 12 inhibitor) is now recommended in most AF patients early after PCI. Although such studies have shown a low absolute incidence of stent thrombosis, they included only a fraction of patients with ACS (ranging from 31 to 62% in different trials), and were largely underpowered to truly assess efficacy in terms of cardioembolic or coronary events, making the confidence about the beneficial net clinical benefit of this strategy in terms of protection from coronary events and stent thrombosis in ACS patients questionable, especially in those submitted to high-complexity PCI.…”
Section: Prevention Of Coronary Ischemic Eventsmentioning
confidence: 99%
“…Indeed, the sample size required to detect a 55% increase with an event rate of 0.7% per year at a two-sided significance level of 0.05 with 90% power would have to include at least 10.500 patients per arm. Moreover, the TAT used as a reference in these meta-analyses [ 27 , 28 ] cannot be considered as the state-of-the-art for coronary protection, since it precludes the use of the new P2Y 12 inhibitors, and is inevitably burdened by a high incidence of hemorrhages. What if DAT were to be compared to the current state-of-the-art DAPT (aspirin + one of the new P2Y 12 inhibitor) instead of TAT, especially in the case of high-risk PCI?…”
Section: Prevention Of Coronary Ischemic Eventsmentioning
confidence: 99%